Design of an inductor-less step-up ac/dc converter for 0.3~V1~MHz vibration energy harvesting - Kei Eguchi; Akira Shibata; Kyoka Kuwahara; Takaaki Ishibashi (Energy Reports, 2020)
For vibration energy harvesting, we propose an inductor-less step-up ac/dc converter in this paper. To realize the inductor-less design, the proposed ac/dc converter consists of two converter blocks: Cockcroft-Walton circuit and charge pump. Unlike existing ac/dc converters for vibration energy harvesting, the proposed ac/dc converter can achieve less electro-magnetic interference (EMI), because no magnetic component is necessary. Furthermore, owing to the Cockcroft-Walton circuit, a full-bridge circuit is not necessary to convert vibration energy. Therefore, small vibration energy, namely, as 0.3~V@1~MHz, can be converted directly to dc voltage. Through theoretical analysis and simulation program with integrated circuit emphasis (SPICE) simulation, the performance of the proposed converter with 6 voltage gain is investigated, where the proposed converter is designed by assuming 0.18μm CMOS process. The proposed converter demonstrates that about 62% power efficiency can be provided, where the output power is 30~μW, the output voltage is about 1.6~V, and the ripple factor is 0.8%. Furthermore, the feasibility of the proposed ac/dc converter is confirmed by breadboard experiments. The inductor-less design provides us to integrate the proposed ac/dc converter into a hybrid IC chip.
Keywords: 330; ac/dc converters; Charge pump; CMOS circuits; Cockcroft-Walton circuit; Inductor-less converters; Vibration energy harvesting